Ratchet Limit Estimation of Pressurized Pipes under Cyclic Bending Moment. (2015) - Peng, H.Y.; Zheng, X.T.; Yu, J.Y.; Xu, J.M.; Wang, C.G.; Lin, W.
Abstract: Analytical ratcheting limits of straight pipes subjected to typical reversed bending and steady internal pressure were deduced theoretically according to the Non-Cyclic Method. The effects of radius ratio on ratcheting limit of pipes were investigated intensively. Results revealed that the obtained ratcheting limits have higher precision than those results obtained by KTA/ASME and RCC-MR code, while the analytical results are still conservative comparing the experiment data due to the strain hardening behavior was not considered. Finally, a corresponding Bree-like diagram was established, which can be used to estimate ratcheting limits of strain hardening pipes conveniently for engineering design.